POLITIK HUKUM KEWARGANEGARAAN INDONESIA: STUDI TERHADAP STATUS WARGANEGARA YANG MENJADI FOREIGN TERORIST FIGHTERS (FTF) ISIS - Kustiwa, Iwa; Harijanti, Susi Dwi; Wulandari, Widati (Faculty of Law, Universitas Pasundan, 2023)
Government policy reflects the extent to which Indonesian citizenship law accommodates the issue of Foreign Terrorist Fighter (FTF)s, as well as future projections of what can be done against FTF based on related laws and regulations, especially those related to citizenship laws. The method used in this study is normative juridical, with data collection through literature study. The results showed that the citizenship status of Foreign Terrorist Fighters from Indonesia based on a human rights perspective, the state can only revoke a person's citizenship based on a court decision. A person's citizenship status is a fundamental right, and a precious right, therefore, the rights of every citizen must be recognized, respected, protected, facilitated, and fulfilled by the state. In solving the problem of citizenship status of former FTF from Indonesia, it is necessary to improve performance and cooperation in the deradicalization process by all elements of the Government and Law Enforcement Officers commanded by the National Counterterrorism Agency and the development of sterile area infrastructure with a high security system to carry out the deradicalization process while carrying out the FTF citizenship status determination trial process. Keywords: Law, Citizenship, Foreign Terrorist Fighters.